2021
DOI: 10.1371/journal.pone.0249197
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: Lymph node morphology in stage II colorectal cancer

Abstract: Background Colorectal cancer is one of the leading causes of cancer-associated morbidity and mortality worldwide. The local anti-tumour immune response is particularly important for patients with stage II where the tumour-draining lymph nodes have not yet succumbed to tumour spread. The lymph nodes allow for the expansion and release of B cell compartments such as primary follicles and germinal centres. A variation in this anti-tumour immune response may influence the observed clinical heterogeneity in stage I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…tumor location, size, T stage and lymphatic nodal characteristics are directly related to surgical range and procedures; therefore, LARS is directly in uenced by these three factors [39][40][41]. But this theory is suggested in our study and the other studies have no mentioned the tumor T stage and nodal classi cation as the risk factors in their researches.…”
Section: Discussionmentioning
confidence: 59%
“…tumor location, size, T stage and lymphatic nodal characteristics are directly related to surgical range and procedures; therefore, LARS is directly in uenced by these three factors [39][40][41]. But this theory is suggested in our study and the other studies have no mentioned the tumor T stage and nodal classi cation as the risk factors in their researches.…”
Section: Discussionmentioning
confidence: 59%
“…Tumor location, size, T stage and lymphatic nodal characteristics are directly related to surgical range and procedures; therefore, LARS is directly influenced by these three factors ( 39 41 ). But this theory is suggested in our study and the other studies have no mentioned the tumor T stage and nodal classification as the risk factors in their researches.…”
Section: Discussionmentioning
confidence: 99%
“…When the adaptive immune response begins, the contractile function of FRC actomyosin is inhibited, facilitating rapid lymph node expansion to accommodate the increased number of activated T and B cells [8]. Previous studies have also shown lymph node follicular hyperplasia in the drainage areas of patients with stage II colon cancer [9], suggesting an association between non-metastatic enlargement of tumordraining lymph nodes and the tumor-adaptive immune response. Recently, some studies have reported that BLNE is a favourable prognostic factor for colorectal cancer [7,10], while other studies have proposed hat it is associated with poorer prognosis [11].…”
mentioning
confidence: 99%